Digital Divide, Digital Inclusion and Inclusive Education - Hamburg, Ileana; Lütgen, Gabriela (Advances in Social Sciences Research Journal, 2019)
Digital divide refers to the gap of unequal accessibility and experience for access and use of modern information and communication technologies; digital inclusion has a focus on a practical, policy-driven approach in this context that addresses the needs of communities as a whole. Inclusive education is a process of strengthening the capacity of education systems to reach out all learners being welcomed in regular classes and to support them to learn, contribute and participate in all aspects of the life in schools and training institutions. Inclusive education is in many European countries at the beginning, even though it has numerous benefits and supports digital inclusion. This chapter presents some aspects of supporting inclusive education through digital technologies, the impact of digital divide and digital inclusion on inclusive education and how could digital platforms support digital inclusion. Some example of European projects with own participation of authors are presented where inclusive educational methodologies and technologies have been developed to minimize the negative impact of digital divide on people with disabilities and support inclusive education and training.